Characteristics of PVP–stabilised NZVI and application to dechlorination of soil–sorbed TCE with ionic surfactant. (January 2020) - Tian, Huifang; Liang, Ying; Yang, Dongmei; Sun, Yifei
Abstract: The characteristics of polyvinylpyrrolidone (PVP)–stabilised nano–zero–valent iron (PVP–NZVI) and its application, combined with surfactant, to trichloroethylene (TCE)–contaminated soil were investigated. Two surfactants (cetyltrimethylammonium bromide [CTAB] and sodium dodecyl sulphate [SDS]) were tested for their ability to enhance the remedial activity of PVP–NZVI in 3 h batch experiments. The prepared PVP–NZVI formed nanoparticles ∼70 nm in diameter. The isoelectric point of PVP–NZVI was about 8.51, similar to the initial pH. X–ray diffraction and X–ray photoelectron spectroscopy analyses revealed that ZVI was the main active component of PVP–NZVI, and carbonised products of the target were observed. The TCE dechlorination efficiency by PVP–NZVI was about 84.73%; the efficiency by PVP–NZVI was about 20% higher when combined with SDS than with CTAB. Therefore, application of PVP–NZVI with SDS represents a potential remediation approach for TCE–contaminated soil. Graphical abstract: Image 1 Highlights: Isoelectric point of PVP-NZVI is close to initial pH value of soil-water system. High concentration of PVP had an advantage to maintain the zero–valent state and reduce the aggregation of NZVI. PVP-NZVI combined with surfactant exhibited fast reduction rate of TCE reduction. TCE was almost completely removed from the soil–water system in 3 h. SDS had better effects on the reductive dechlorination of TCE by PVP-NZVI.